Efficacy of Metformin Therapy in Management of Polycystic Ovary Syndrome - Sarah Fatima, Shafaq Ismail Makhdoom, Sasui Phulpoto, Areesha Qamar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Earlier analysis shows that metformin is beneficial clinically in treating polycystic ovary syndrome (PCOS) by reducing hyperinsulinemia. Aim: The goal of this study was to determine the importance of metformin in modifying amenorrhea/ oligomenorrhea and anovulation within six months in women with polycystic ovary syndrome and hyperinsulinemia. Another goal was to evaluate hyperinsulinemia and weight loss with metformin in the studied people. Methods: This randomized controlled trial was held at the Obstetrics and Gynecology department of the Jinnah Postgraduate Medical Centre Karachi for one-year duration from July 2020 to July 2021. The study included 160 women who met the biochemical and clinical conditions for hyperinsulinemia and PCOS. Two females stopped taking the drug due to abdominal cramps, diarrhoea and nausea. Other excluding factors were inadequate adherence in one female women and use of other medications in two women. One female had anomalous levels of serum creatinine and was omitted from the analysis. So, 154 total patients were studied. 500 mg / day metformin orally was started and was held at 500 mg for six-months. FSH, serum LH, fasting insulin, fasting glucose and creatinine were measured in addition to ultrasound and body weight. After 6 months: fasting insulin levels, menstrual cycles, body weight and serum progesterone on day 21 were measured. Serum androgen levels remains high in PCOS along with Prolactin levels and the LH/FSH ratio may be greater than 2 times. So, these parameters were assessed after six months of metformin to determine the improvement in symptoms of oligomenorrhea and amenorrhea in PCOS and clinically with improvement in menstrual cycle. Results: Subsequently 6 months of treatment with metformin, 135 out of 154 (84%) women had regular periods, 24 of which were in the ovulation range of luteal progesterone (> 30 nmol / L). The average fasting insulin concentration among patients on metformin therapy reduced from 22.5 micro-U / ml to 21.01 micro-U / ml (p = 0.00).